De plaats en de situatie van de jonge kunstenaar in de hedendaagse samenleving : Bedenkingen. - Rau, Daan; De Cauter, Lieven; Hoedemakers, Caroline; Vermassen, Jan; Demaegd, Frank; Elias, Willem; Pas, Johan ([S.l] : [s.n.], 1994)
De Vylder, Paul ; Tuymans, Luc ; Borremans, Michaël ; Clinckx, Christine ; Decq, Bart ; Demeyere, Benjamin ; Dendauw-Imbo, Claude ; De Smet, Gery ; Gobyn, Luk ; Molleman, Linda ; Schraepen, Kurt ; Vanbillemont, Gerry ; Verlinden, Greet.
Van 7 maart tot 15 april 1994
kunstcatalogus